Calving Event Led to Changes in Phytoplankton Bloom Phenology in the Mertz Polynya, Antarctica. Issue 11 (1st November 2020) - Liniger, Guillaume; Strutton, Peter G.; Lannuzel, Delphine; Moreau, Sebastien
Abstract: Polynyas are subject to variability in winds and ocean circulation and are important sites of ecological productivity. In February 2010, the B09B iceberg collided with the Mertz Glacier Tongue (MGT), calving a 78 × 40‐km giant iceberg which modified the icescape and primary productivity of the Mertz polynya. In this study, we use satellite ocean color and sea ice concentration to investigate the variability, trends, and drivers of phytoplankton blooms in the Mertz polynya since 1997. During the bloom, over 21 years, we found (i) a later ice retreat time, (ii) an increase in sea ice concentration, (iii) a decrease in open‐water period, (iv) a later bloom start, and (v) a decrease in bloom duration. Our results suggest that major postcalving changes in the physical characteristics of the polynya, mainly its icescape, are the primary drivers of phytoplankton phenology. More specifically, the MGT calving event resulted in significant seasonal and regional changes, with higher eastern chl‐ a and mean summer chl‐ a postcalving. While satellite data are useful to study long‐term variability in these inhospitable areas, they only focus on the ocean surface and are obscured by ice and clouds. Additional subsurface parameters from seal tags, gliders and moorings in the southernmost polar regions would strengthen our comprehension of phytoplankton and physical changes in ocean dynamics that may have far‐reaching consequences, from global circulation to carbon export. Plain Language Summary: Polynyas are the most productive areas in the Southern Ocean and play a role in the global oceanic circulation. Evaluating how unexpected and dramatic changes impact biology and chemical cycles in these areas is critical to understand the potential future impact such events may cause on a larger scale. In this paper, we investigated the impact of the calving of a major glacier tongue in the Mertz polynya on the phytoplankton bloom using satellite data. Significant changes happened after the calving event: (i) the bloom duration and open water period time decreased, (ii) the start of the bloom and the retreat of sea ice were delayed, and (iii) the chlorophyll‐ a (the major phytoplankton pigment which indicates the phytoplankton biomass) and the sea ice concentration increased. These findings show that natural changes can impact the timing of phytoplankton growth that may have consequences for the rest of the ecosystem, from Antarctic krill to baleen whales. Key Points: The calving of the Mertz Glacier tongue led to changes in the phytoplankton bloom and sea ice phenology in the polynya Our study highlights regional differences in the polynya Natural changes in icescape like in the Mertz polynya will soon be accelerated, with consequences for ocean biogeochemistry and ecology